TEKNIK HYDROPRIMING DENGAN MENGGUNAKAN SENYAWA ORGANIK TERHADAP PENINGKATAN VIGOR BENIH BENIH MANGGIS - Syafruddin Syafruddin; Said Imran AK; Nurzuhairawaty Nurzuhairawaty (Jurnal Agrista, 2003)
An experiment was conducted at seed science and technology laboratory, agriculture Faculty, Unsyiah from Mei to Agustus 2003. The objectives of this research were to evaluate the effect of organic compound on improving of mangosteen seed vigor. The research was calcilated with non factorial, based on Complete Randomized Design with four replications. The treatments were control and organic compound of five levels, i.e. coconut oil, corn, banana, carrot, and tomato. Each extract concentration used was 15%. Variables such as growth potential, seedling growth rate, speed of germination, and uniformity of growth were measured. The results showed that all organic compound significantly increased growth potential, seedling growth rate, speed of germination, and uniformity of groth. The coconut milk treatment is the best to increase mangosteen seed vigor.